Determining the dielectric constant of injection-molded polymer-matrix nanocomposites filled with barium titanate. (December 2020) - Brito, Daniel; Quirarte, Guadalupe; Morgan, Joshua; Rackoff, Eleanor; Fernandez, Michael; Ganjam, Dithi; Dato, Albert; Monson, Todd C.
Abstract : Abstract: Barium titanate (BTO) is a ferroelectric perovskite with potential in energy storage applications. Previous research suggests that BTO dielectric constant increases as nanoparticle diameter decreases. This report recounts an investigation of this relationship. Injection-molded nanocomposites of 5 vol% BTO nanoparticles incorporated in a low-density polyethylene matrix were fabricated and measured. Finite-element analysis was used to model nanocomposites of all BTO sizes and the results were compared with experimental data. Both indicated a negligible relationship between BTO diameter and dielectric constant at 5 vol%. However, a path for fabricating and testing composites of 30 vol% and higher is presented here.